2020
DOI: 10.34768/amcs-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for quaternion-based 3D rotation

Abstract: In this work a new algorithm for quaternion-based spatial rotation is presented which reduces the number of underlying real multiplications. The performing of a quaternion-based rotation using a rotation matrix takes 15 ordinary multiplications, 6 trivial multiplications by 2 (left-shifts), 21 additions, and 4 squarings of real numbers, while the proposed algorithm can compute the same result in only 14 real multiplications (or multipliers-in a hardware implementation case), 43 additions, 4 right-shifts (multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The rotation is accomplished by the use of a quadratic, and the vector satisfies Equation (11), which is obtained and then matched to the path point . This part of the method regarding the rotation of quaternions is referred to in [ 20 ] and will not be repeated here. …”
Section: Methodsmentioning
confidence: 99%
“…The rotation is accomplished by the use of a quadratic, and the vector satisfies Equation (11), which is obtained and then matched to the path point . This part of the method regarding the rotation of quaternions is referred to in [ 20 ] and will not be repeated here. …”
Section: Methodsmentioning
confidence: 99%
“…A rotation is the motion of a rigid body around a fixed point and preserves one point differently. Based on Euler's rotation theorem from geometry in 3D, a rigid body's displacement is equivalent to a single rotation about some axis that runs through the fixed point [24,25]. The theoretical and applied rotation matrices are discussed in rigid body mechanics, robotics, spacecraft attitude dynamics, navigation, threedimensional, and computer graphics.…”
Section: Rotation Matrixmentioning
confidence: 99%
“…When creating a number system capable of representing rotation in threedimensional space, William Hamilton proposed a new number system, namely a four-dimensional system; one actual number (R) and three imaginary numbers i, j, and k, called Quaternions [29 -31]. Due to the property of quaternions, each quaternion unit represents the rotation of an object in three dimensions (3D) [24], [32 -36]. The quaternion formula has the following equation (7).…”
Section: Rotation Matrixmentioning
confidence: 99%
“…Many commonly used algorithms, ranging from simple real-valued to hyper complex algorithms are employed (2)(3)(4) to analyze the image characteristics. In (5)(6)(7)(8) the authors exploit octonion linear canonical transform and Quaternion based algorithm to investigate the mathematical analysis of an image signal. Takahashi et al (9) suggested Remarks on Octonion-valued Neural Networks to control the Robot applications.…”
Section: Introductionmentioning
confidence: 99%